Malignant Seminoma in Two Unilaterally Cryptorchid Stallions. Issue 3 (10th March 2015) - De Lange, V; Chiers, K; Lefère, L; Cools, M; Ververs, C; Govaere, J
Contents: Two unilateral cryptorchid stallions were referred to the clinic because of chronic debilitating condition with emaciation. Rectal examination, and ultrasound and gross examination revealed in both animals an abdominal mass, caudally of the kidney, and multiple nodules spread over the abdomen. Histologic analysis revealed an intra‐abdominal malignant seminoma with intraperitoneal and renal metastasis. Interestingly, a seminoma was also present in the descended testis of the draught horse.